Laboratory scale electrostatically assisted wet scrubber for controlling dust in livestock buidlings - Almuhanna, E. A.; Maghirang, Ronaldo G.; Murphy, James P.; Erickson, Larry E. (American society of agricultural and biological engineers, 2009)
A prototype electrostatically assisted particulate wet scrubber (EPWS) for controlling dust in livestock buildings was developed and tested under laboratory and field conditions. Under laboratory conditions, the EPWS with the negatively-charged water spray had significantly higher particle removal efficiency (79%) than either the uncharged wet scrubber (58%) or the control (i.e., only the fan was operated; 21%). There was no significant difference in removal efficiency between the negatively-charged EPWS (79%) and the positively-charged EPWS (73%). For the negatively-charged EPWS, an optimum ratio between the air flow rate and amount of water spray for each specific mixing volume existed in which the removal efficiency decreased as the air flow rate increased. Field tests in a swine building proved that the EPWS was effective in removing airborne dust.
Keywords: Indoor air quality; Dust control; Charged water spray; Electrostatic force